Linking Green Intellectual Capital and Green Culture to Competitive Advantage through Green Innovation - Ayu Aryista Dewi; Komang Adi Kurniawan Saputra (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the mediating role of green innovation in the relationship between green intellectual capital and green culture on competitive advantage in the hotel industry in Bali, Indonesia. Methodology: A causal-explanatory research design was employed, with data collected from 106 managers of three- to five-star hotels using purposive sampling technique. The study is grounded in the Natural Resource-Based View, and the data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results: The findings indicate that green intellectual capital and green culture have a positive and significant effect on green innovation. Green innovation has a strong, positive, and significant impact on competitive advantage. Green innovation also significantly mediates the relationship between green intellectual capital and green culture on competitive advantage, indicating a full mediation. Control variables such as gender and hotel classification had no significant effect on competitive advantage. Conclusions: Green innovation functions as a crucial dynamic capability that converts intangible environmental resources, such as knowledge assets and cultural values, into tangible competitive advantages. Limitations: This study is limited by its sample size of 106 respondents and its focus on three- to five-star hotels in Bali, which may restrict the generalizability of the findings to other regions or hotel types. Contributions: This study contributes to the literature by extending the application of the Natural Resource-Based View in the hospitality sector. Practically, it highlights the importance of prioritizing green innovation as a key mechanism for leveraging intellectual capital and green culture to achieve sustainable competitive advantage.